In Between Contemporary Approaches to Genre: the Case of the Trauma Novel - Teliban, Cătălina-Diana (International Journal of Language and Literary Studies, 2023)
The elusive notion of genre has long been disputed in the field of literary studies, with certain voices going as far as to argue for disregarding the notion altogether in the study of literature. This article goes through the relevant schools of thought about genre and its functions, settling finally on one contemporary approach devised by Amy Devitt, which is then upgraded and employed in the analysis of two of the most famed contemporary trauma novels: On Earth We’re Briefly Gorgeous by Ocean Vuong and A Tale for the Time Being by Ruth Ozeki. The hypothesis of the paper is that the thorough and specialized knowledge about trauma which has been widely made available to society at large transpires in the writings of contemporary authors at the formal level of novel creation, a level which, if understood correctly, serves to uncover more meaning from the novels, producing a deeper level of philological understanding, as the formalities of the trauma novel contemporarily seem to mimic psychotherapeutic trauma approaches.